An Analysis of the Continuance Intention of QRIS Users in Southeast Sulawesi Using the Expectation Confirmation Model (ECM) - Nisrina Hamid; Muhammad Sofian Maksar; Yuan Swastika; Andi Meuthia Zulfaidah Tenripadang (Jurnal Manajemen dan Kewirausahaan, 2025)
The rapid growth of digital payment technologies has transformed how people conduct financial transactions in Indonesia. As one of the leading innovations, QRIS (Quick Response Code Indonesian Standard) plays a key role in promoting a cashless society across various regions. This study aims to analyze users’ continuance intention toward the use of QRIS in Southeast Sulawesi through the lens of the Expectation Confirmation Model (ECM) framework. Given the growing adoption of digital payment systems, the research seeks to systematically identify and evaluate the key determinants influencing users’ sustained usage behavior. Quantitative methods were applied by collecting data from 250 respondents who are QRIS users. The results of the analysis show that expectation confirmation and perceived usefulness have a significant influence on user satisfaction. However, despite high satisfaction, no significant relationship was found between satisfaction and intention to continue using. In addition, habit was shown to contribute positively to intention to continue. These findings highlight the importance of user experience and trust in digital services. This study recommends further exploration to understand other factors that may influence intention to continue using in the context of digital payment systems.